(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article is an analysis of the current state of increasing the country’s financial potential through attracting foreign investment. The article analyzes and results of the volume of attracted foreign investments and their share in the country’s gross domestic product, as well as the target areas determined by the head of our state to increase the volume of attracted investments in the future.